VTP-CSMA: A virtual token passing approach for real-time communication in IEEE 802.11 wireless networks - moraes, r (2007)
Currently, there is a trend towards the implementation of industrial communication systems using wireless networks. However, keeping up with the timing constraints of real-time traffic in wireless environments is a hard task. The main reason is that real-time devices must share the same communication medium with timing unconstrained devices. The VTP-CSMA architecture has been proposed to deal with this problem. It considers an unified wireless system in one frequency band, where the communication bandwidth is shared by real-time and non-real-time communicating devices. The proposed architecture is based on a virtual token passing (VTP) procedure that circulates a virtual token among real-time devices. This virtual token is complemented by an underlying traffic separation mechanism that prioritizes the real-time traffic over the non-real-time traffic. This is one of the most innovative aspects of the proposed architecture, as most part of real-time communication approaches are not able to handle timing unconstrained traffic sharing the same communication medium. A ring management procedure for the VTP-CSMA architecture is also proposed, allowing real-time stations to adequately join/leave the virtual ring.